Analysis of structural behavior during collision event accounting for bow and side structure interaction - Aditya Rio Prabowo; Dong Myung Bae; Jung Min Sohn; Ahmad Fauzan Zakki; Bo Cao; Qing Wang (Theoretical and Applied Mechanics Letters, 2017)
The main goal of this study was to investigate the effects of selected ship collision parameter values on the characteristics of the absorbed energy in several ship collision scenarios. Non-linear simulations were performed using a finite element method (FEM) to obtain virtual experiment data. In the present research, the size of the side damage from a collision phenomenon were measured and used to verify the numerical configuration together with the calculation results using an empirical equation. Parameters in the external dynamics of a ship collision such as the location of the contact point and velocity of the striking ship were taken into consideration. The internal energy and deformation size on the side structure were discussed further in a comparative study. The effects of the selected parameters on several structural behaviors, namely energy, force, and damage extent were also observed and evaluated in this section. Stiffener on side hull was found to contribute significantly into resistance capability of the target ship against penetration of the striking bow. Remarkable force during penetration was observed to occur when inner shell was crushed as certain velocity was applied in the striking bow.